2016
DOI: 10.3345/kjp.2016.59.12.490
|View full text |Cite
|
Sign up to set email alerts
|

Accidental ingestion of E-cigarette liquid nicotine in a 15-month-old child: an infant mortality case of nicotine intoxication

Abstract: Electronic cigarettes are novel tobacco products that are frequently used these days. The cartridge contains liquid nicotine and accidental poisoning, even with a small oral dose, endangers children. We present here a mortality case of a 15-month-old child who ingested liquid nicotine mistaking it for cold medicine. When the emergency medical technicians arrived, she was found to have pulseless electrical activity. Spontaneous circulation was restored after approximately 40 minutes of cardiopulmonary resuscita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
40
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 12 publications
(14 reference statements)
1
40
0
1
Order By: Relevance
“…6 In 1 case report, a 15 month-old child died after ingesting a dose of 4.1 mg/kg of liquid nicotine. 10 The 1 death in our study was previously reported. 7 Fatalities from liquid nicotine poisonings could be prevented by limiting the volume and concentration of liquid nicotine packaged in containers to a sublethal dose for an average young child.…”
Section: Figuresupporting
confidence: 58%
“…6 In 1 case report, a 15 month-old child died after ingesting a dose of 4.1 mg/kg of liquid nicotine. 10 The 1 death in our study was previously reported. 7 Fatalities from liquid nicotine poisonings could be prevented by limiting the volume and concentration of liquid nicotine packaged in containers to a sublethal dose for an average young child.…”
Section: Figuresupporting
confidence: 58%
“…Oral ingestion of nicotine e‐cigarette fluid has been noted in numerous attempted suicides and was the method of at least two documented successful suicides, with an additional suicide following intravenous injection of e‐liquid (Table ). There has also been at least one reported death following accidental ingestion of nicotine e‐liquid in a 15‐month‐old . The child ingested 5 mL (50 mg) of liquid nicotine and despite immediately vomiting the patient developed cardiopulmonary arrest and hypoxic brain damage .…”
Section: Summary Of Literature Case Reports Of Fatal Intoxications Wimentioning
confidence: 99%
“…6 The child ingested 5 mL (50 mg) of liquid nicotine and despite immediately vomiting the patient developed cardiopulmonary arrest and hypoxic brain damage. 6 The lethal adult oral dose of nicotine is often quoted as 30-60 mg (corresponding to an oral lethal dose 50% (LD 50 ) of around 0.8 mg/kg); however, a 2014 paper by Mayer states that this dose is based upon dubious 19th-century data and should be revisited with more recent overdose survival data suggesting the lethal dose of oral nicotine is more than 0.5 g or an LD 50 of 6.5 mg/kg. 7 There are also two cases in the literature detailing burns caused by the spontaneous explosion of the battery in e-cigarettes.…”
mentioning
confidence: 99%
“…[9][10][11][12] Although most calls involve minimal toxic effects, 11,13 case reports have documented severe neurologic symptoms, anoxic brain injury and death resulting from unintentional pediatric ingestion of e-juice. 14,15 The primary known hazard associated with ENDS exposure is nicotine, which is absorbed through the skin, alveoli and oropharyngeal/gastrointestinal mucosa. 14 Although nicotine is most commonly associated with central nervous system excitation, excessive or prolonged exposure can result in loss of receptor specificity and paradoxical inhibition, causing cholinergic toxicity and blockade at the neuromuscular junction.…”
mentioning
confidence: 99%
“…14,15 The primary known hazard associated with ENDS exposure is nicotine, which is absorbed through the skin, alveoli and oropharyngeal/gastrointestinal mucosa. 14 Although nicotine is most commonly associated with central nervous system excitation, excessive or prolonged exposure can result in loss of receptor specificity and paradoxical inhibition, causing cholinergic toxicity and blockade at the neuromuscular junction. The lethal adult dosage of nicotine is estimated at less than 1 mg/kg.…”
mentioning
confidence: 99%